Law's relations a relational theory of self, autonomy, and law - Nedelsky, Jennifer (New York : Oxford University Press, 2011)
Jennifer Nedelsky claims that we must rethink our notion of autonomy, rejecting the usual vocabulary of control, boundaries and individual rights. If we understand that we are fundamentally in relation to others, she argues, we will recognize that we become autonomous with others.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 20, 2012).
Includes bibliographical references and index.
Keywords: Law -- Psychological aspects; Interpersonal relations; Autonomy (Psychology)